2000
DOI: 10.1007/bf02353761
|View full text |Cite
|
Sign up to set email alerts
|

Obturator hernia: embryology, anatomy, surgery

Abstract: Summary" Obturator hernia is relatively rare and typically affects frail, elderly, multiparous women. Most obturator hernias contain small intestine, usually a knuckle of ileum ; obstruction is often partial. A history of previous episodes of acute obstruction followed by remission is common. Strangulation eventually occurs, and surgical intervention is the only effective treatment. Pain in the medial aspect of the thigh, sometimes radiating to hip and knee joints (Howship-Romberg sign), and loss of the adduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 56 publications
0
55
1
3
Order By: Relevance
“…Some authors do not believe that the obturator canal fat plug is a pathological entity, as they have found it on all dissections and therefore consider it a cushion for the obturator nerve (Skandalakis et al, 2000). Despite careful dissection we found that only 22% of cadavers had fat plugs, and a larger series has found an even lower rate (Anson et al, 1950).…”
Section: Discussionmentioning
confidence: 84%
“…Some authors do not believe that the obturator canal fat plug is a pathological entity, as they have found it on all dissections and therefore consider it a cushion for the obturator nerve (Skandalakis et al, 2000). Despite careful dissection we found that only 22% of cadavers had fat plugs, and a larger series has found an even lower rate (Anson et al, 1950).…”
Section: Discussionmentioning
confidence: 84%
“…When the lacunar ligament is opened, this branch vessel that passes behind it, above Cooper's ligament, could be damaged product of the staples or tacks placed on Cooper's ligament, leading to potentially fatal bleeding (Sabuncuoglu et al, 2015). The unexpected presence of the AOA can become a problem for the orthopaedic surgeon, urologist, gynecologist and general surgeon, any of which can perform surgical procedures in this area (Skandalakis et al, 2000). However, in clinical practice the incidence of excessive bleeding of these variant vessels is extremely low (Darmanis et al).…”
Section: Discussionmentioning
confidence: 99%
“…The obturator foramen consists of the superior pubic ramus on the superior pubic body, inferior ramus on the medial, and ischial ramus on the inferior side [13]. The obturator foramen in the anteromedial pelvic wall is positioned in the inferior portion of acetabulum, typically located between the origin of the medial umbilical and lateral umbilical fold in the abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%